The forty-seven ronin the vendetta in history - Tucker, John Allen (Cambridge University Press, 2018)
The Forty-Seven Rōnin vendetta is one of the most famous incidents in Japanese history, but it is also one of the most misunderstood. John A. Tucker seeks to provide a credible account of the vendetta and its afterlife in history. He suggests that, when considered historically and holistically, the vendetta appears as a site of contested cultural ground, with conflicts, disagreements, and debates characterizing its three-century history far more than cultural unanimity about its values, virtues, and icons. Tucker narrates the incident as the historical event that it was, within the context of Tokugawa social, political, cultural, and spiritual history, before exploring the vendetta as conflicted cultural ground, generating a steady flow of essays, novels, plays, and ideologically driven expressions intrinsic to the course of Japanese history. This engaging, accessible study provides insights into ways in which events and debates from early modern history have continued to inform developments in modern Japan